2023
DOI: 10.2147/ijgm.s421913
|View full text |Cite
|
Sign up to set email alerts
|

A Revised PADMA Scoring System for Predicting in-Hospital Mortality in Acute Coronary Syndrome Patient

Raymond Bernardus,
Miftah Pramudyo,
Mohammad Akbar

Abstract: Background In order to predict in-hospital mortality in ACS (Acute Coronary Syndrome) patients based solely on clinical examination, this study compares the shock index (heart rate divided by systolic blood pressure) variable in PADMA (PADjadjaran Mortality in Acute Coronary Syndrome) with the modified shock index (heart rate divided by mean arterial pressure) score. The predictive efficacy of the PADMA score in predicting in-hospital mortality in ACS patients has been in doubt up until recently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Innovative reperfusion techniques beyond conventional strategies, such as distal embolic protection devices, bioresorbable scaffolds, and microvascular interventions, have been discussed. These techniques optimize reperfusion outcomes by reducing distal embolization, promoting vessel healing, and addressing microvascular dysfunction [29,30]. Innovative reperfusion techniques offer personalized approaches to MI management, reducing complications and improving patient outcomes.…”
Section: Discussion and Implications: Advancements In Myocardial Infa...mentioning
confidence: 99%
See 4 more Smart Citations
“…Innovative reperfusion techniques beyond conventional strategies, such as distal embolic protection devices, bioresorbable scaffolds, and microvascular interventions, have been discussed. These techniques optimize reperfusion outcomes by reducing distal embolization, promoting vessel healing, and addressing microvascular dysfunction [29,30]. Innovative reperfusion techniques offer personalized approaches to MI management, reducing complications and improving patient outcomes.…”
Section: Discussion and Implications: Advancements In Myocardial Infa...mentioning
confidence: 99%
“…The use of EPDs has been shown to be particularly beneficial in patients with complex lesion morphology, high thrombus burden, and vulnerable plaques. Clinical trials, such as the EMERALD study, have demonstrated the safety and efficacy of EPDs in improving myocardial perfusion, reducing infarct size, and lowering the risk of major adverse cardiac events [30].…”
Section: Distal Embolic Protection Devicesmentioning
confidence: 99%
See 3 more Smart Citations